AB0498 Mid-term clinical result of treatment with biologics in patients with rheumatoid arthritis to prevent structural damage of knee joints. (23rd January 2014) - Kojima, T.; Funahashi, K.; Takahashi, N.; Kato, D.; Matsubara, H.; Hattori, Y.; Ishiguro, N.
Abstract : Background: Biologics brings the target of RA treatment from just care of pain to remission. In Japan, treatment with Bio was stared at 2003 in clinical practice. Mid-long term results of the treatment are still unclear. Especially, inhibitory effects on destruction of weight-bearing large joints such as knee, which should cause much loss of ADL and QOL of patients, are unknown at all. Objectives: The purpose of this study is to estimate the effectiveness of biologics on prevention of destruction of knee joints for five years retrospectively. Methods: We studied retrospectively the 156 RA patients (312 knee joints) who were started the treatment with biologics (infliximab 80 cases, etanercept 76 cases) until May 2008. We collected the data including disease activity (DAS28-CRP), presence or absence of arthritis in knee joint by physical examination, Larsen grade of knee joints at initiation and latest observation, and the date of total knee arthroplasty (TKA). Survival rate of knee joint was determined using Kaplan-Meier Method. Results: Baseline characteristics were shown in Table 1. We detected arthritis in 141 knee joints, no arthritis in 130 knee joints and 41 TKA at baseline. The patients with arthritic knee joint had significant higher disease activity, compared to the patients with non-arthritic knee joints (DAS28-CRP; 5.42 vs 4.96, p=0.031). 49% of arthritic knees were estimated as Larsen III-IV while 99% of non-arthritic knees were Larsen 0-II. The survival rate of arthritic knees at 5 years was 60% while that of non-arthritic knees was 90% (Fig.1 ). In these years until 2008, 40% of the knee joints had been destructed as (Larsen III-IV) at initiation of Bio. 36% of arthritic Larsen 0-II-graded knee joints at baseline still had arthritis in the knee at latest observation or had been performed TKA. Finally, progression of joint destruction was detected in 58% of these knees. However, 60% of arthritis in Larsen 0-II graded knee joint at baseline was suppressed. The knee joints, of which arthritis was suppressed, had less progression of joint destruction. In the other hand, only 9% of non-arthritic Larsen 0-II-graded knee joints at baseline had arthritis at latest observation or had been performed TKA (just 1 case). It is significant low rate. However, progression of joint destruction was detected in 67% of arthritic knee joints, which had no arthritis at baseline (Fig.2). Conclusions: Bio could have significant effectiveness for suppression of arthritis and joint destruction in the knee joints. If arthritis in the knee joint was continued even after treatment with Bio, joint destruction could progress for 5 years (mean) observation. The more aggressive and earlier intervention is critical to prevent the destruction of knee joints with arthritis. Disclosure of Interest: T. Kojima: None Declared, K. Funahashi: None Declared, N. Takahashi: None Declared, D. Kato: None Declared, H. Matsubara: None Declared, Y. Hattori: None Declared, N. Ishiguro Speakers Bureau: Abbott Japan, Chugai Pharmaceutical, Daiichi Sankyo Pharmaceutical, Eisai, Mitsubishi Tanabe Pharma, Pfizer Japan, Takeda Pharmaceutical